Challenges Faced by English Teacher in Teaching: Case Study of Junior High School in Banjarnegara Regency - Hari Widi Utomo; Tatsuya Kusakabe; Achmad Sultoni; Dhina Setyowati (STKIP Singkawang, 2020)
Teaching English is not a very easy job and becomes a challenging task for the Junior High School teacher in Banjarnegara regency that is located in a mountainous area and the majority of the people love to speak their mother tongue in their daily life. The main purpose of this study was to investigate the challenges faced by an English teacher in the teaching as well as what the solution/recommendation they made. This study employed the qualitative methods in which questionnaires and interview guide utilized and hundred and twenty-five (N=125) teachers were purposely and conveniently sampled from Junior High School English teachers in Banjarnegara regency. The results revealed that the challenges faced in teaching English are divided into four parts. The first challenges were from the teachers. These challenges are less of teaching material, teaching design, classroom management, ICT skill, many teaching administration, job loaded, and memory decrease. The second was from the students. Those are lack of vocabulary, loss of motivation, and juvenile delinquencies. The third was from schools. Schools had limited facilities, which can be utilized by teachers and students in teaching activities such as; limited dictionary, projector, and language laboratory. The fourth was from the parents. Many parents from the village have low education and future vision so it influenced their children's education. The study also gives three recommendations for succeeding in teaching English such as; (1) teachers should make teaching contract at the beginning of the semester, (2) principals send teachers joining to MGMP meeting and Continuous Professional Development activity, (3) schools give motivation to students and parents periodically.